(untitled) (Research, Society and Development, 2024)
This article addresses the importance of nursing supervision in shaping students’ ethical thinking. The supervising nurse plays a crucial role in the ethical and professional development of students, ensuring quality care and fostering the growth of the supervisee. The study proposes two objectives: to describe a nursing supervision situation and to analyze the ethical role of the supervisor in students’ ethical formation. The adopted methodology is descriptive and reflective. Successful supervision depends on the quality of the relationship between supervisor and supervisee, as well as constant reflection on practice. Supervisors face challenges such as integrating theory and practice, supporting student development, and promoting their ethical thinking. A case study elucidates the importance of ethical supervision. A student faced ethical issues while caring for a patient. After joint reflection, the student understood the importance of informed consent and respect for patient autonomy. The supervisor played a fundamental role in guiding the student and promoting their critical thinking. In conclusion, ethical supervision is decisive for the development of students’ ethical thinking in nursing. Reflection on practice, mediated by supervisors, is essential to promote students’ critical and ethical thinking, empowering them to face the challenges of the profession responsibly and ethically.